2023
DOI: 10.31083/j.rcm2405147
|View full text |Cite
|
Sign up to set email alerts
|

Urine High-Sensitive Troponin T—Novel Biomarker of Myocardial Damage in Children

Abstract: Background: The use of high-sensitive cardiac troponin T (hsTnT) in urine as a marker of cardiac damage in children has not yet been reported. Elimination of cardiac troponins is dependent on renal function; persistently increased serum hsTnT concentrations were observed among individuals with impaired renal function. The aim of this study was to investigate serum and urine hsTnT levels and its correlation in infants and children younger than 24 months of age after cardiac surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, since there are no currently available assays that are certified to measure urine cTn concentrations, we believe that assays with characteristics such as limit of blank (LoB) are good enough to measure cTn concentrations in urine samples with sufficient precision and accuracy. Earlier works indicated that this method is applicable [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since there are no currently available assays that are certified to measure urine cTn concentrations, we believe that assays with characteristics such as limit of blank (LoB) are good enough to measure cTn concentrations in urine samples with sufficient precision and accuracy. Earlier works indicated that this method is applicable [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…cTnT and cTnI concentrations were also determined in urine using the same protocol described above for their determination in serum or plasma [8,11].…”
Section: Methodsmentioning
confidence: 99%